E-Transaction Point Of Sales (Pos) With Fuzzy Tsukamoto Algorithm At Pt. Samihasa Kita - Irvan Ardiansyah; Dewi Handayani Untari Ningsih (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2023)
PT. Samihasa Kita is a glass product distributor company that was founded in 1989, which is located in the city of Semarang, Central Java, with sales area coverage in Central Java, D.I Yogyakarta, Jakarta, and Kalimantan. So far, PT Samihasa Kita has an erratic amount of demand for goods, as a result, sometimes the number of goods produced for sale with the goods purchased by consumers is not balanced. This resulted in PT Samihasa Kita not getting the maximum profit. Based on this problem, Fuzzy Tsukamoto logic was chosen to determine the optimal daily production amount. By using fuzzy logic can be determined the relative size of the production of goods. The Fuzzy Tsukamoto method can also be used to forecast sales in the coming month based on the amount of inventory. Thus the amount of production and demand for goods PT. Samihasa Kita is predictable and balances transactions. This research aims to be able to predict demand and procurement of goods that will have an impact on optimizing revenue at PT. Samihasa Kita.